Identity Security Threats: An Analysis Of The Speech Act In Donald Trump Military Excellence Policy - Septiyana Razak Priyatna; Maulana Rifai (Jurnal Komunikasi, 2025)
This study examines the policy of military excellence under the administration of Donald Trump, 2.0. This study uses a descriptive qualitative method with an approach; Case studies and critical discourse analysis techniques. The study examined the narrative in the text of Trump's statement, when consolidating "LGBT" groups as threats. By highlighting gender identity and sexual orientation, which has been politicized as a national security issue. The theoretical framework of this research uses speech act theory by (J.L. Austin), and securitization by (Buzan and Waever) to review the representation of policy by political authorities in national security. This research shows that the discourse of securitization has developed during Trump's time in office, (1) Initiation through declaratives on social media, (2) Formalization of policy documents, through presidential memorandums, and (3) The existence of authority, with a narrative of "burden", "disruption" and "radical ideology" that is the opposite of military discipline. This study concludes that Trump's policy on transgender military personnel is a form of securitization that uses rhetoric and language in political dynamics.